Effect of dehulled lupin seeds in feed mixture on muscle protein quality of ducklings - Eva Straková; Lucie Všetičková; Pavel Suchý; Martin Kutlvašr (Czech Journal of Animal Science, 2025)
The aim of the study was to prepare and test the effect of diets with 50% and 100% replacement of soybean meal with dehulled seeds of white lupin (Lupinus albus) variety Zulika. One hundred and eighty Cherry Valley duckling were divided to control group (C) and two experimental groups E50 (50% replacement of soybean meal with dehulled white lupin meal) and E100 (100% replacement of soybean meal with dehulled white lupin meal). There were evaluated the production parameters and the amino acid spectrum of breast and thigh muscles up to 42 days of age. The effect of diets containing lupin meal had no negative effect on the yield of duckling. In particular, positively can be evaluated higher growth rate in the experimental groups compared to the control (C 3.22 ± 0.28 kg, E50 3.40 ± 0.27 kg, E100 3.48 ± 0.28 kg), at the same time significantly lower mortality in the experimental groups compared to the control (C 5.88%, E50 1.47%, E100 1.49%) and, except for E100, minimal differences in feed conversion ratio (C 2.33 kg/kg, E50 2.27 kg/kg, E100 2.71 kg/kg). Feeding diets based on lupin meal resulted in the reduction of most essential and non-essential amino acids (P ≤ 0.05) in the dry matter content of both breast and thigh muscle (E50, E100). Lupine meal-based diets positively influenced ducks' health, which was reflected by lower mortality rate in the experimental groups. Therefore, the results show that diets based on lupin meal had a positive effect on the health and welfare of intensively fattened ducks and that they affected positively the economic aspect of breeding.